Control of thiocarbamate-resistant rigid ryegrass (Lolium rigidum) in wheat in southern Australia. (10th September 2019) - Brunton, David J.; Boutsalis, Peter; Gill, Gurjeet; Preston, Christopher
Abstract: Two field experiments were conducted during 2018 at Paskeville and Arthurton, South Australia, to identify effective herbicide options for the control of thiocarbamate-resistant rigid ryegrass in wheat. Dose–response experiments confirmed resistance in both field populations (T1 and A18) of rigid ryegrass to triallate, prosulfocarb, trifluralin, and pyroxasulfone. T1 and A18 were 17.9- and 20-fold more resistant to triallate than susceptible SLR4. The level of resistance detected in T1 to prosulfocarb (5.9-fold) and pyroxasulfone (4-fold) was lower compared to A18, which displayed 12.1- and 7.8-fold resistance to both herbicides, respectively. Despite resistance, the mixture of two different preplant-incorporated (PPI) site-of-action herbicides improved rigid ryegrass control and wheat yield compared to a single PPI herbicide only. Prosulfocarb + triallate and prosulfocarb + S -metolachlor + triallate did not reduce rigid ryegrass seed set when compared to prosulfocarb applied alone at the higher rate (2, 400 g ai ha –1 ). Pyroxasulfone + triallate PPI followed by glyphosate (1, 880 g ai ha -1 ) as a weed seed set control treatment reduced rigid ryegrass seed production by 93% and 95% at both sites, respectively. These herbicides also significantly improved grain yield of wheat at Paskeville (22%) and Arthurton (38%) compared to the untreated.